RNAi-mediated knockdown of two orphan G protein-coupled receptors reduces fecundity in the yellow fever mosquito Aedes aegypti - Keyes-Scott, Nia I.; Swade, Kyle R.; Allen, Lena R.; Vogel, Kevin J. (Frontiers in Insect Science, 2023)
G protein-coupled receptors (GPCRs) control numerous physiological processes in insects, including reproduction. While many GPCRs have known ligands, orphan GPCRs do not have identified ligands in which they bind. Advances in genomic sequencing and phylogenetics provide the ability to compare orphan receptor protein sequences to sequences of characterized GPCRs, and thus gain a better understanding of the potential functions of orphan GPCRs. Our study sought to investigate the functions of two orphan GPCRs, AAEL003647 and AAEL019988, in the yellow fever mosquito, Aedes aegypti. From our phylogenetic investigation, we found that AAEL003647 is orthologous to the SIFamide-2/SMYamide receptor. We also found that AAEL019988 is orthologous to the Trapped in endoderm (Tre1) receptor of Drosophila melanogaster. Next, we conducted a tissue-specific expression analysis and found that both receptors had highest expression in the ovaries, suggesting they may be important for reproduction. We then used RNA interference (RNAi) to knock down both genes and found a significant reduction in the number of eggs laid per individual female mosquito, suggesting both receptors are important for Ae. aegypti reproduction.